Preparing Early Childhood Educators for Blending Practices in Inclusive Classrooms - Donegan-Ritter, Mary; Kohler, Frank W. (Journal of the American Academy of Special Education Professionals, 2017)
Preparing early childhood teachers for inclusion requires the blending of high quality developmentally appropriate practices with environmental adaptations and individualized instructional practices. This article describes how a field experience was redesigned to incorporate evidence based practices in teaming and collaboration, environment and instruction. A STEM learning center was the context for this case study on a preservice teacher and preschool child with special needs. Changes to the physical, social and temporal environment set the stage for promoting communication goals and led to increased child engagement and language use. Implications and recommendations for how to structure unified early childhood/early childhood special education teacher preparation programs for blended practices are discussed.